A Study On The Fast Pyrolysis Of Jackfruit Peel To Bio-Oil In A Drop-Type Fixed Bed Reactor - Kaliappan, Thayasree (Universiti Sains Malaysia, 2018)
Energy demand is increasing due to rapid growth in population and leads to depletion of fossil fuels. To prevent the energy crisis, this study explores fast pyrolysis of Jackfruit peel into bio-oil in a drop-type fixed bed reactor. This is because, the biomass considered very effective renewable resources compared to conventional fossil fuels where it can be used for energy production which potentially sustainable and reduce environmental pollution. Fast pyrolysis serves as promising techniques to dispose of agriculture waste and to get bio-oil, bio-char and syngas simultaneously. The experiment was carried out at different reaction temperature (350-650 'C), particle size (0.25-2 mm) and nitrogen flow rate (200-400 mL/min). The highest bio-oil yield (57.86wt%) was obtained at 550 'C with Jackfruit Peel (JFP) waste size of 0.5-1 mm and 200 ml/min of nitrogen gas flow rate. Preliminary experiment was conducted using thermogravimetric analyzer (TGA) to determine the proximate analysis of JFP. Then, elemental composition and higher heating value of the feedstock and bio-oil (550 'C) were determined and compared. Additionally, the FTIR analysis and GC-MS analysis were carried out on bio-oil to investigate the functional group and chemical composition of bio-oil respectively. The chemical characterization of bio-oil results provide some promising insight into the application of bio-oil in chemical plant, which could be useful as a chemical feedstock and used as combustion fuels for electricity.